Children's Social Behavior Related to Law - Miftah, Mohammad (Jurnal Sosial Sains dan Komunikasi, 2023)
To deal with children who are related to the law, of course, all parties must be actively involved and contributive. There is also a need for synergistic integration between psychology and law to make the best decisions for children. If a child with ABH is forced to undergo trial, then moral support from the surrounding environment and positive stimulation is needed to rehabilitate the child's behavior for the better. Thus, between parents and the state have the same portion to jointly handle children in conflict with the law. This study uses descriptive analytical research specifications with analytical methods using normative qualitative methods, while the results of this study explain that children who commit criminal acts or Children in Conflict with the Law (ABH) cannot be handled only from a legal perspective which ends in court and prison consequences. However, it must also be seen from the surrounding environment that causes children to commit these criminal acts. Because basically children are still psychologically unstable and cannot think carefully about the consequences of their bad deeds. If a child is in trouble with the law, then based on the Child Protection Act, the police should still use the principles of restorative justice and discretion to deal with ABH properly and optimally. Children have rights that are specifically different from adults because of their unstable physical and mental conditions. In many cases, children need special treatment and protection, especially against actions that could be detrimental to their development and that of society. Children need other parties such as family, society, government and the state to support the natural growth and development of children.